2011
DOI: 10.1016/j.placenta.2011.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Meeting report of the first conference of the International Placenta Stem Cell Society (IPLASS)

Abstract: The International Placenta Stem Cell Society (IPLASS) was founded in June 2010. Its goal is to serve as a network for advancing research and clinical applications of stem/progenitor cells isolated from human term placental tissues, including the amnio-chorionic fetal membranes and Wharton's jelly. The commitment of the Society to champion placenta as a stem cell source was realized with the inaugural meeting of IPLASS held in Brescia, Italy, in October 2010. Officially designated as an EMBO-endorsed scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
10
0
4
Order By: Relevance
“…Therefore, modulating macrophage activities has been designed as a new therapeutic approach to promote tissue regeneration (Sica and Mantovani, ). The fact that hAMTCs and CM could switch the differentiation of pro‐inflammatory M1‐macrophages into a M2 anti‐inflammatory/immune‐suppressive phenotype could reveal the beneficial effects observed in different in vivo models (Parolini et al , ; Silini et al , ). Indeed, macrophage‐mediated resolution has been observed after treatment with amniotic‐derived cells or MSCs from different sources in liver fibrosis (Manuelpillai et al , ), multiple sclerosis (Liu et al , ), lung fibrosis (Murphy et al , ; Cargnoni et al , ; Tan et al , ), tendon lesions (Mauro et al , ) and skin wound healing (Zhang et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, modulating macrophage activities has been designed as a new therapeutic approach to promote tissue regeneration (Sica and Mantovani, ). The fact that hAMTCs and CM could switch the differentiation of pro‐inflammatory M1‐macrophages into a M2 anti‐inflammatory/immune‐suppressive phenotype could reveal the beneficial effects observed in different in vivo models (Parolini et al , ; Silini et al , ). Indeed, macrophage‐mediated resolution has been observed after treatment with amniotic‐derived cells or MSCs from different sources in liver fibrosis (Manuelpillai et al , ), multiple sclerosis (Liu et al , ), lung fibrosis (Murphy et al , ; Cargnoni et al , ; Tan et al , ), tendon lesions (Mauro et al , ) and skin wound healing (Zhang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing evidence has demonstrated that cells isolated from the amniotic membrane of human term placenta possess interesting immunomodulatory properties that make them an attractive tool for the cellular treatment of immune‐related disorders. Indeed, we and others have demonstrated that human amniotic mesenchymal cells (hAMSCs) and epithelial cells (hAECs), as well as conditioned medium (CM) derived from their culture, possess anti‐inflammatory and anti‐proliferative properties that affect cells of the innate and adaptive immune systems (Parolini et al , ). These properties include the in vitro ability to suppress T cell proliferation (Li et al , ; Wolbank et al , ; Magatti et al , ; Rossi et al , ; Pianta et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these are the promotion of reepithelization, the modulation of cell differentiation and formation of new vessels, and a reduction in fibrosis, apoptosis, and inflammation. [ 14 15 16 17 ] Currently, amnion-derived tissues have been obtained with the objective of using them in the clinical field. These are widely used for skin burns and wound healing in traumatology and general surgery.…”
Section: Therapeutic Applications Of Amniotic Stem Cellsmentioning
confidence: 99%
“…Several investigations have evaluated the differentiation potential of cells from both the amnion and amniotic fluid, demonstrating that these cells exhibit high plasticity [1]. The majority of studies target amnion stem cells, revealing their tendency to promote re-epithelization, modulate differentiation and angiogenesis, and reduce inflammation, apoptosis, and fibrosis following transplantation [1][2][3][4]. Accumulating evidence have now similarly shown stemness of the lesser studied amniotic fluid-derived stem cells (AFSCs).…”
Section: Introductionmentioning
confidence: 99%